Imagined Agency: Technology, Unpredictability, and Ambiguity. - Ferguson, John Robert (Contemporary Music Review, 2013)
My work focuses on technologically mediated music-making, in this article I present and interpret audio-visual documents of my performance practice, and reflect on the conceptual and aesthetic motivations that underpin the creative process. Exploring the role of resistance and inertia in the field of performing technologies is the main agenda; questions around the location of human agency and its decipherability are foregrounded throughout. Although various theoretical perspectives inform the discussion, these perspectives are (mostly) embedded at the heart of the practical activity, and should not be considered as after-the-fact justification, but as essential elements in unfolding a practice that configures making as thinking and thinking as doing. I hope that the black-and-whiteness of text does not form an obscuring smokescreen of grey around my work, and that the reader finds the discursive and metaphorical approach to be illuminating. The text is supported by video clips which appear as supplementary material accessible online via the article's Supplementary tab on the Taylor & Francis website (http://www.tandfonline.com/loi/gcmr).